The Role of Chemotherapy Status, Absolute Lymphocyte Count and Neutrophil Lymphocyte Ratio as Biomarkers of Candidiasis in Lung Cancer Patients - Muhamad Yusuf Musthafa; Iin Noor Chozin; Ungky Agus Setyawan; Teguh Wahyu Sardjono; Noorhamdani AS (Perhimpunan Dokter Paru Indonesia (PDPI)/The Indonesian Society of Respirology (ISR), 2023)
Background: Gradually, fungal infections are growing and have become a medical concern. Candida species are one of the most common pathogens in immunocompromised patients, such as those with lung cancer causing invasive fungal disease. Early diagnosis of candidiasis is critical for patient care in lung cancer patients. Anti-mannan IgM and IgG biomarkers are used to diagnose candidiasis. This study aims to determine the relationship between chemotherapy status, absolute lymphocyte count, and neutrophil-lymphocyte ratio to antimannan IgM and IgG.Methods: A correlative analytic cross-sectional study was conducted on 37 lung cancer patients with positive candida sputum cultures in Dr. Saiful Anwar Malang Hospital. The 37 patients were examined for total lymphocyte level, neutrophil-lymphocyte ratio, anti-mannan IgM, and IgG. Data analysis used a contingency coefficient to determine the relationship between chemotherapy status, absolute lymphocyte count, and neutrophil-lymphocyte ratio to anti-mannan IgM and IgG.Results: This study showed a positive correlation between chemotherapy status with anti-mannan IgM and IgG, although insignificant (p>0.05). However, there was a significant correlation between total lymphocytes and anti-mannan IgG (p=0.000;α=0.05) and between neutrophil-lymphocyte ratio and antimannan IgM (p=0.004; α=0.05).Conclusion: The study revealed that chemotherapy status, absolute lymphocyte count, and neutrophil-lymphocyte ratio could be a biomarker of candidiasis, so lung cancer patients with a history of chemotherapy, lymphopenia, and increased neutrophil-lymphocyte ratio should consider receiving antifungals earlier.